WATER-EMULSION SEPARATING COVERINGS FOR PRODUCTION OF BARS BY HEATED MOUNTING - A. M. Mihaltsov; A. A. Pivovarchik; G. A. Kuijan (Литьë и металлургия)
The production of water-emulsion lubrication on basis of organosilicon polymers for production of cores by heated tool is described, and also its physical properties are studied and given.